Tiger snake (Notechis scutatus) envenomation in a horse. Issue 9 (27th August 2013) - Cullimore, AM; Lester, GD; Swindells, KL
<x xml:space="preserve">Abstract</x> Background A 7‐year‐old Thoroughbred gelding presented with muscle fasciculation, reluctance to move, profuse sweating, tachycardia, tachypnoea and a localised, unilateral swelling on the muzzle. History and physical examination were suggestive of snake envenomation. Methods A sandwich ELISA for the detection of snake venom was performed on serum and urine samples. Result The test performed on urine confirmed a diagnosis of tiger snake envenomation. Conclusion The response to treatment with antivenom and supportive medical therapy was excellent.